2012
DOI: 10.1073/pnas.1212592109
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a midlife crisis in great apes consistent with the U-shape in human well-being

Abstract: Recently, economists and behavioral scientists have studied the pattern of human well-being over the lifespan. In dozens of countries, and for a large range of well-being measures, including happiness and mental health, well-being is high in youth, falls to a nadir in midlife, and rises again in old age. The reasons for this U-shape are still unclear. Present theories emphasize sociological and economic forces. In this study we show that a similar U-shape exists in 508 great apes (two samples of chimpanzees an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 36 publications
2
80
0
Order By: Relevance
“…This is quite clearly shown in the Stone et al (2010) study that reveals different patterns depending on whether a global measure of well-being, a positive hedonic well-being measure or a negative hedonic well-being measure (such as "worry" or "sadness") is used. Recent use of more "objective" measures of subjective well-being, such as use of antidepressants (Blanchflower and Oswald, 2011) or reports of apes' well-being by their keepers (Weiss et al, 2012), tend to support the U-shape.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is quite clearly shown in the Stone et al (2010) study that reveals different patterns depending on whether a global measure of well-being, a positive hedonic well-being measure or a negative hedonic well-being measure (such as "worry" or "sadness") is used. Recent use of more "objective" measures of subjective well-being, such as use of antidepressants (Blanchflower and Oswald, 2011) or reports of apes' well-being by their keepers (Weiss et al, 2012), tend to support the U-shape.…”
Section: Discussionmentioning
confidence: 99%
“…Three recent studies have used "non-subjective" data to assess the U-shape relation, namely Blanchflower and Oswald (2011), Lang et al (2011), and Weiss et al (2012.…”
Section: U-shaped Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, age has a u-shaped relationship with life satisfaction, with a turning point at the age of 53 (see e.g. Blanchflower and Oswald, 2008;Weiss et al, 2012).…”
Section: Personal Characteristicsmentioning
confidence: 99%
“…Existing studies provide empirical support that some of the observed U shaped pattern is due to biology (Weiss et al, 2012), emotional wisdom and regulation (Baltes and Baltes, 1990;Carstensen et al 2003;Scheibe and Blanchard-Fields, 2009), and unmet expectations (Schwandt, 2016). While it is difficult to know whether any of the suggested mechanisms also interact with reduced feelings of envy observed in later years, one reason why the inclusion of envy may not alter the estimated U shape is purely mathematical in nature.…”
Section: Why Does Envy Not Mediate the Ageing Relationship?mentioning
confidence: 99%